2022
DOI: 10.1136/bmjsem-2021-001270
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent stretching and rubber band strengthening exercises do not reduce overuse shoulder injuries: a cluster randomised controlled trial with 579 handball athletes

Abstract: ObjectivesHandball is associated with a high risk of overuse shoulder injury. This study investigated if an injury prevention programme effectively reduces overuse injury to the throwing shoulder of handball athletes.Methods61 men’s and women’s handball teams (u-19 and senior athletes) were cluster-randomised into an intervention and a control group in the 2019–2020 season. Players of the intervention group regularly carried out an injury prevention programme. Both groups documented overuse shoulder injuries v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Therefore, a recent meta-analysis [ 16 ] suggests, that future studies should focus on the effects of resistance training modalities on the upper extremity muscle fascicle geometry due to its strong relationship with athletic performance, injury, and force production. However, it seems that the majority of exercise interventions aimed at reducing the risk of shoulder injury and discomfort target functional changes in flexibility and strength without substantially reducing the injury rate [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a recent meta-analysis [ 16 ] suggests, that future studies should focus on the effects of resistance training modalities on the upper extremity muscle fascicle geometry due to its strong relationship with athletic performance, injury, and force production. However, it seems that the majority of exercise interventions aimed at reducing the risk of shoulder injury and discomfort target functional changes in flexibility and strength without substantially reducing the injury rate [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…No systematic reviews were identified. Eight RCTs1 43–49 and one prospective study50 were included (table 2). The highest quality of evidence for a preventative effect was observed for Oslo Sports Trauma Research Center (OSTRC) Shoulder Injury Prevention programme,1 the Shoulder Control programme,47 a throwing injury prevention programme43 and the FIFA 11+ shoulder injury prevention programme (moderate quality of evidence) 44.…”
Section: Resultsmentioning
confidence: 99%
“…A GIRD above 20° and an isometric strength ratio of 0.78 is typically found for a throwing shoulder with high risk for injury ( Lubiatowski et al, 2018 ; Achenbach et al, 2020 ). In handball, there is a gap in prevention studies for the shoulder ( Achenbach et al, 2020 ), while prevention studies are desperately needed because commonly prescribed exercise strategies for the shoulder do not reduce the risk of overuse injuries in handball ( Achenbach et al, 2022 ). To the best of our knowledge, only Andersson et al (2017) investigated the preventive effects of a strengthening program for the external rotators and found an increase in strength and a 28% decrease in shoulder injuries, providing a little indication of the potential for shoulder prevention exercises.…”
Section: Introductionmentioning
confidence: 99%